Resposta :
[tex]\text x^4-6\text x^2+\text c=0\\\\ \text x^4-6\text x^2+9+\text c =9 \\\\ (\text x^2-3)^2=9-\text c \\\\ \text x^2-3=\pm\sqrt{9-\text c} \\\\ \underline{\text{Primeira restri{\c c}{\~a}o }}: \\\\ 9-\text c > 0 \to \boxed{\text c < 9} \\\\ \underline{\text{Continuando}}: \\\\ \text x^2 = 3\pm\sqrt{9-\text c} \\\\ \text x=\pm\sqrt{3\pm\sqrt{9-\text c}} \\\\ \text{Pegando uma das ra{\'i}zes para analisar}: \\\\\ \sqrt{3-\sqrt{9-\text c}} >0\\\\ 3-\sqrt{9-\text c}>0 \\\\ \sqrt{9-\text c}<3 \\\\ 9-\text c<9[/tex]
[tex]-\text c<0 \to \boxed{\text c>0}[/tex]
Portanto :
[tex]\huge\boxed{\ 0<\text c<9\ }\checkmark[/tex]
Letra E